Gain Consumer Insight With Generative AI - Arora, Neeraj; Chakraborty, Ishita; Nishimura, Yohei (MIT Sloan Management Review, 2026)
Marketing research traditionally costs tens of thousands of dollars and takes months. Large language models are changing this by compressing timelines from months to days. LLMs enable synthetic consumer “digital twins” for rapid concept testing, AI-moderated interviews for qualitative research at scale, and powerful analysis of unstructured data. These tools allow smaller research teams to conduct larger studies while maintaining quality, thus enabling more frequent testing and experimentation.